FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU DISFUNGSIONAL AUDITOR SERTA PENGARUHNYA TERHADAP KUALITAS AUDIT (AUDITOR DI SURABAYA) - Maria V. Irene Herdjiono (EKONOMI & SOSIAL, 2012)
This research study factors that influence auditor’s dysfunctional behavior and how dysfunctional behavior influence audit quality . That factors are time budget pressures, working paper review and supervision. Auditor’s dysfunctional behavior mirror from behavior of premature sign off, under-reporting of time and audit quality reduction behavior. The objectives of study to have more understanding about auditor’s dysfunctional behavior and factors that influence it and impact of auditor’s dysfunctional behavior to audit quality. The result of the simple linear regression concluded that time budget pressures, supervision influence auditor’s dysfunctional behavior premature sign off, under-reporting of time and audit quality reduction behavior and working paper review influence auditor’s dysfunctional premature sign off and audit quality reduction behavior. Also this study indicates  auditor’s dysfunctional behavior premature sign off, under-reporting of time and audit quality reduction behavior influence audit quality.